The Embedded Systems Landscape. - Wolf, Wayne (Computer (00189162), 2007)
The article presents an overview of embedded systems computing and introduces several articles in the current issue about the subject. Two primary challenges facing designers of embedded systems are achieving high performance in real time, and reducing power consumption. Meeting these challenges will require changes in both the hardware and software of embedded systems. Desktop computer architecture may no longer be the most relevant model for embedded systems. Requirements of operating in real time will demand that software be able to accurately estimate performance and power consumption.